Geomagnetic Gradient Bionic Navigation Based on Parallel Approach Method (Xibei Gongye Daxue Xuebao, 2018)
Priori geomagnetic information is important to the geomagnetic navigation. However in practice, the precision of the geomagnetic information is a greatly constraint to the development of the geomagnetic navigation. In order to solve this problem, this paper present a geomagnetic gradient bionic navigation method based on parallel approach without any priori information. Inspired by the evidence that many creatures can navigate using the Earth magnetic field, the navigation process can be considered as a convergence of multi-objective problem, and develop the bionics navigation model. By introducing the parallel approach method to the navigation process, the heading angle can be estimated with the information of magnetic field gradient. The simulation results show the proposed method is able to navigation effectively without magnetic priori information, just rely on the actual geomagnetic measurement, which has implies potential application in the future.